Pengaruh Work Overload terhadap Nurse Performance dengan Burnout sebagai Variabel Intervening di Rumah Sakit X Surabaya - Astria Primadhani Pamungkas; Ahmad Rizki Sridadi (UNUSA Press, 2020)
Job stress is a serious phenomenon that refers to workplace characteristics that threaten workers. Nursing has been identified as a job that has high stress level. Nursalam (2011) states that nurses who are given excessive workload can have an impact on burnout. Burnout occurs when people feel that the resources they value are threatened, they try to maintain those resources (Maslach and Leiter, 2016). Burnout can result in decreased nurse performance/Burnout can cause decreasing of nurse performance. The purpose of this study was to determine the effect of work overload on nurse performance directly nor indirectly. This study using quantitative approach and nonprobability sampling technique with saturated sampling of 40 low care inpatient service nurses in X Hospital Surabaya. Data analysis techniques using path analysis. The results showed that there was a significant negative effect between work overload and nurse performance directly nor indirectly.